Development and contextual analysis of a person-centered professional practice model in a home care service in French-speaking Switzerland - Mabire, Cedric; Panchaud, Sandra; Wey, Jessica; Wicht, Justine (Frontiers in Health Services, 2025)
BackgroundThe Swiss healthcare system faces increasing challenges with an aging population and rising prevalence of chronic conditions, necessitating better-coordinated care delivery, particularly in home care settings.ObjectivesThis study aimed to develop (objective 1) and conduct a contextual analysis for implementation (objective 2) of a person-centered professional practice model for home care services in French-speaking Switzerland.MethodsA multi-method approach was used. For objective 1, concept mapping with 157 healthcare professionals (86% response rate) was conducted to develop the model. For objective 2, a contextual analysis was guided by the Intervention Mapping framework, involving focus groups with stakeholders (n = 14) and field validation with frontline staff (n = 6). Data analysis included both quantitative and qualitative methods.ResultsThe concept mapping process identified 13 core values rated on importance (scale 1–5), with health promotion scoring highest (4.4) and interprofessionalism lowest (3.7). Implementation analysis revealed key facilitators including leadership support (83% agreement) and barriers such as linguistic/cultural differences. Eight implementation strategies were identified and validated through a Delphi process, including continuous training (67% strong agreement) and safety culture promotion (83% strong agreement).ConclusionsThe study demonstrates that developing and implementing a person-centered professional practice model is feasible in home care settings when supported by strong leadership commitment and structured implementation strategies. The model's alignment with the Person-centred Practice Framework of McCance and McCormack provides theoretical validation while offering practical guidance for implementation.